2015
DOI: 10.1007/s00520-015-3001-5
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase inhibitor induced musculoskeletal syndrome: a significant problem with limited treatment options

Abstract: We conclude that aromatase inhibitor induced musculoskeletal syndrome is a significant issue for Australian women and is an important reason for treatment discontinuation. Women use a variety of interventions to manage this syndrome; however, their efficacy appears limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 42 publications
0
41
1
2
Order By: Relevance
“…Other trials have also reported on the influence of preexisting joint and muscle/limb pain on musculoskeletal pain syndrome during treatment with AIs . The severity of pain during AI treatment has also been evaluated in other studies .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other trials have also reported on the influence of preexisting joint and muscle/limb pain on musculoskeletal pain syndrome during treatment with AIs . The severity of pain during AI treatment has also been evaluated in other studies .…”
Section: Discussionmentioning
confidence: 99%
“…The most common and typical AEs associated with AIs are vasomotor and general climacteric symptoms, as well as musculoskeletal pain syndrome . The latter, involving myalgia and arthralgia, is usually the reason for early discontinuation of AIs and is therefore a topic of special interest …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials of adjuvant AIs report AIMSS in up to 36% of patients; however, community‐based series report considerably higher rates. In a survey of Australian women taking AIs, 82% of women reported AIMSS 15 . Any joint can be affected but hands, hips, feet and knees were most commonly involved.…”
Section: Aromatase Inhibitor Musculoskeletal Syndromementioning
confidence: 99%
“…Studies have demonstrated that 25–32% of women will discontinue AI prior to completing a 5-year course, and in studies where 10 years of AI therapy was recommended, adherence decreased to 38% [24]. A common cause for AI discontinuation is AI-associated musculoskeletal symptoms (AIMSS), which result in an 18–24% discontinuation rates during the first 2 years [2, 5]. …”
Section: Introductionmentioning
confidence: 99%